CCNA Cloud Library : CLDFND 210-451 and CLDADM 210-455. - Santana, Gustavo Alessandro Andrade; Jackson, Chris, 1973-; Safari eBooks ([Place of publication not identified] : Cisco Press, 2016)
"More than 14 hours of video instruction on Cloud fundamentals, Cloud technologies, Cloud administration and operations, Cloud monitoring and reporting, Cloud troubleshooting as well as cloud computing concepts, service models, infrastructure solutions, and architectures."--Resource description page.
CCNA Cloud CLDFND 210-451 / Gustavo Santana -- CCNA Cloud CLDADM 210-455 / Chris Jackson.
Title from resource description page (Safari, viewed March 18, 2016).
Presenters, Gustavo A. A. Santana, Chris Jackson.
Keywords: Cloud computing; Electronic data processing personnel -- Certification; Computer networks -- Examinations; Electronic books